Carmen in russian poetry of the Silver Age. The problem of the intersemiotic relationship - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The aim of this article is to analyze two literary works of the Silver Age that are the poetic interpretation of Carmen story: the poem Carmen by A. Blok and the verse “Carmen” by I. Severyanin. Analyzing both literary works we pointed on different motives from the novel by Merimee and the opera by Bizet. We noticed that Blok and Severyanin not only simply had used well known situations but also had proposed their own interpretation of Carmen based on the intersemiotic relationship between literature, music and opera art.